Thermal solar desalination : methods and systems - Belessiotis, Vassilis; Kalogirou, Soteris; Delyannis, E. (Academic Press is an imprint of Elsevier, 2016)
Thermal Solar Desalination: Methods and Systems presents numerous thermal seawater desalination technologies varying from the very simple, easy to construct and operate solar stills, to the more advance membrane and indirect distillation methods. All types of solar thermal desalination technologies are presented in detail to enable readers to comprehend the subject, from design details to enabling further research to be carried out in this area. The various units used in desalination are outlined, along with diagrams of all detailed working principles of desalination methods and systems. The authors consider the economic aspects of these processes, demonstrating successful implementation of desalination units suitable for areas where supplies of fresh water in natural ways is limited or non-existent.